Government control of market of hard biofuel as one of factors of balanced use of nature - Чурілов, Д. Г.; Калініченко, В. М.; Калініченко, А. В.; Малинська, Л. В. (Scientific Progress & Innovations, 2012)
The article considers a possibility of using biomass in form of fuel granules as an alternative to traditional energy resources. The analysis of existing standards for the manufacture of fuel granules in Europe and USA as well as basic requirements for this type of biofuel was carried out. Presented the difference between current and previous standards. The economic expediency of adoption of related standards in Ukraine was represented. The necessity of introduction of quality standards for biofuel producers in Ukraine, particularly for was proved.